Flaubert’s Provocation - Culler, Jonathan (Text Matters: A Journal of Literature, Theory and Culture, 2017)
Madame Bovary, which was scandalous in its own day for its focus on the adultery of a provincial woman, has had a strange, complex fate. Flaubert remade the image of the novelist, as pure artist, for whom style was all that mattered, and disrupted novelistic technique, in ways that critics and writers have found exemplary, treating this as the novel novelists cannot overlook; yet for readers Madame Bovary is not a “book about nothing” but provides a searing portrait of provincial life and of the condition of women. The vividness and complexity of the character Flaubert created here made Emma a type: a sufferer of “Bovarysme.” Flaubert’s revolutionary notion that a trivial subject was as good as a noble subject for a serious novel was taken to be connected to the democratic notion that every human subject is as worthy as another and allowed to have desires. Yet, while promoting Emma as a valid subject of literature, equal to others, Flaubert writes against the attempt to democratize art, to make it enter every life, and renders trivial the manifestations of this subject’s desires, while making her an exemplary figure.